(untitled) (Bangladesh Journal of Livestock Research, 2020)
This study was undertaken to know the effect of silage and soybean straw based Total Mixed Ration (TMR) on the growth performances of growing bull calves. 30 growing bull calves were divided into 5 treatment groups considering their initial body weight 111.30±6.67 to115.66±10.69 kg and age 24 to 26 months, respectively. Five types of TMR were prepared with different roughage and concentrate ratios (R: C) as T1=70:30, T2=60:40, T3=50:50, T4=40:60, T5=30:70. TMR intake, DM intake, CP intake of animals in T2 group was significantly (P<0.001) higher. Significantly higher (P<0.01) DM and CP digestibility were observed in T2. No significant differences observed for live weight gain. The ADG was slightly higher in T2 group (0.860 kg/day) but no significant differences were found among the treatments. Based on the results, it may be concluded that using a 60:40 (R: C) TMR can be formulated for fattening bulls for proper growth and maintenance. Bangladesh J. of Livestock Res. 21-25: 82-88, 2018